DECISION-MAKING IN TABLE GAMES - Norieva , Aziza Jasur qizi (Innovative Development in Educational Activities, 2023)
In this article, problem tasks related to tabular issues of game theory and process research are considered, and the article can be used by students of scientific educational institutions, young people, and professors. They can learn methods that determine game balance.